FORMULASI DAN EVALUASI SIFAT FISIK DARI SEDIAAN FACE WASH YANG MENGANDUNG EKSTRAK AIR BUNGA KESUMBA TURATE (Carthamus tinctorius L). - Hamka, Nurhafizah; Hasrawati, Andi; Zulkarnain, Iskandar; Mirawati, Mirawati (Fakultas Farmasi UMI, 2023)
Carthamus tinctorius L. has antioxidant activity and contains polyphenols and flavonoids so it can be used for skin care such as face wash. The aim of this research is to formulate and evaluate a face wash preparation from water extract of Carthamus tinctorius L flowers that is physically stable. Carthamus tinctorius L water extract face wash preparations have been made in 4 formulas with different gelling agent variations, namely Carbopol and HPMC with concentrations of 1% and 1.5%. Preparation tests that have been carried out include organoleptic tests, homogeneity tests, pH tests, syneresis tests, viscosity tests, flow properties and stability tests. Research results have shown that Carthamus tinctorius L water extract can be made into a face wash preparation with a thick consistency, odorless and brown in color. The preparation that has been made is homogeneous and has a pH between 3-6. The viscosity ranges from 30.4 – 159.8 P with a plastic flow type with a yield value between 13.5 – 32.9 dyne/cm2. Syneresis tests have shown water loss between 7.13 – 19.7%. The results of the stability test have shown that the formula with gelling agent HPMC at a concentration of 1.5% has pharmaceutical properties that do not change after stress conditions.